Commencement - Gabriel Pulido (Journal Committed to Social Change on Race and Ethnicity)
This special issue on poetry invites readers into a reflective engagement with language, art, and the emotional resonance of creative expression. Assembling a powerful collection of poetic voices, Pulido encourages a reorientation toward art as a catalyst for personal and cultural movement—emotionally, intellectually, and spiritually. The issue resists academic formalism, instead cultivating space for vulnerability, care, and interpretation. By foregrounding the significance of words and embodied connection, it positions poetry as vital within and beyond educational spaces.